Family-clinician shared decision making in intensive care units: Cluster randomized trial in China. Issue 6 (June 2022) - Liu, Xinchun; Humphris, Gerald; Luo, Aijing; Yang, Mingshi; Yan, Jin; Huang, Shaohua; Xiao, Siyu; Lv, Ailian; Wu, Guobao; Gui, Peigen; Wang, Qingyan; Zhang, Yudong; et al.
Highlights: The FCSDM intervention improved families' satisfaction. The FCSDM intervention decreased families' depression. The FCSDM intervention shortened patients' length of stay in ICU. The FCSDM intervention improved clinicians' collaboration. Abstract: Objective: To investigate if a Family-Clinician Shared Decision-Making (FCSDM) intervention benefits patients, families and intensive care units (ICUs) clinicians. Methods: Six ICUs in China were allocated to intervention or usual care. 548 patients with critical illness, 548 family members and 387 ICU clinicians were included into the study. Structured FCSDM family meetings were held in the intervention group. Scales of SSDM, HADS, QoL2 and CSACD were used to assess families' satisfaction and distress, patients' quality of life, and clinicians' collaboration respectively. Results: Comparing the intervention group with the control group at post-intervention, there were significant differences in the families' satisfaction (P = 0.0001), depression level (P = 0.005), and patients' quality of life (P = 0.0007). The clinicians' mean CSCAD score was more positive in the intervention group than controls (P < 0.05). There was no significant between-group differences on ICU daily medical cost, but the intervention group demonstrated shorter number of days' stay in ICU (P = 0.0004). Conclusion: The FCSDM intervention improved families' satisfaction and depression, shortened patients' duration of ICU stay, and enhanced ICU clinicians' collaboration. Practice implications: Further improvement and promotion of the FCSDM model are needed to provide more evidence to this field in China.